تواصل الأسرة مع المدرسة، الأهمية والعوائق - جيماوي, نتيجة (Changement Social; No 06 (2019): revue change social, 2019)
إن التعاون بين الأسرة والمدرسة بات أمرا ضروريا من أجل النجاح والنهوض بالعملية التربوية والتعليمية، لأن حياة التلميذ الدراسية لا تنفصل عن حياته اليومية في البيت، وتعد المدرسة شريكا أساسيا في عملية التنشئة الاجتماعية للتلميذ بل وتعتبر الفاعل المؤثر الأكثر أهمية في حياته. ولذا تعتبر مجالس أولياء التلاميذ القنوات أو الصيغ التربوية الأبرز لتحقيق هذا التواصل والترابط بين البت والمدرسة ؛ وفي هذه المداخلة سنوضح أهمية التواصل مع أولياء التلاميذ بالنسبة للمؤسسات التربوية الجزائرية، وكذلك شرح بعض أسباب تغيب الأولياء من وجهة نضرهم ،والتي قد تساعد في فهم الآليات الانسب مع التلاميذ والتي تعود على رفع المستوى الدراسي لأبنائهم. إن زيارة الاولياء المستمرة للمدرسة تكشف عن جوانب هامة من شخصية التلميذ، كالجانب الصحي، النفسي، الانفعالي؛ ففي كثير من الأحيان لا يتمكن المعلم من اكتشافها في حجرة الدرس؛ وإنما من خلال مثل هذه اللقاءات والتي تعود حتما على المردود الدراسي للتلميذ. ومنه نطرح التساؤل التالي: ما أهمية تواصل أولياء التلاميذ مع المعلم وسؤلي المؤسسات التربوية، وما هي أهم العوائق التي تقف أمام هذا التواصل والتي تنعكس سلبا على الجودة التعليمية والتربوية للتلميذ؟ The cooperation between the family and the school is necessary for the success and advancement of the educational process, because the student's life is not separated from his daily life at home, and the school is a key partner in the process of socialization of the student and is the most influential actor in his life. In this intervention we will explain the importance of communication with parents of students for the Algerian educational institutions, as well as explain some of the reasons for the absence of the parents from the point of view, which may help to understand the most appropriate mechanisms With students who are returning to raise the level of education for their children. The visit of the school's continuing parents reveals important aspects of the student's personality, such as the health, psychological, and emotional aspects; often the teacher is not able to discover them in the classroom, but through such meetings, which inevitably return to the student's educational return. We ask the following question: What is the importance of continuing the parents of the students with the teacher and ask the educational institutions, and what are the most important obstacles that stand in front of this communication, which negatively affect the educational quality of the student?